Penerapan Model Pembelajaran Bahasa Arab Berbasis SAVI (Somatis, Auditori, Visual, Intelektual) dalam Meningkatkan Hasil Belajar pada Peserta Didik - Koderi, Koderi (Universitas Islam Negeri Raden Intan Lampung, 2018)
Abstract: This research is focused on to cope with the problems commonly encountered by students in learning Arabic including low retention, low motivation, lack of skills and unsatisfactory learning achievement due to insufficient learning facilities and variations. This study is aimed at acquiring obtaining empirical data